UPPER PLEISTOCENE MAMMAL ASSEMBLAGE FROM SU CONCALI QUARRY (SAMATZAI, SOUTHERN SARDINIA, ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2017)
A mammal assemblage discovered in a fissure filling located in a quarry near the village of Samatzai (Campidano, southern Sardinia, Italy) is described herein. The following taxa are reported: Microtus (Tyrrhenicola) henseli, Rhagamys orthodon, Prolagus sardus, Asoriculus sp., Cynotherium sardous and Praemegaceros (Nesoleipoceros) cazioti. The assemblage (“Microtus (Tyrrhenicola)” Faunal Complex, Dragonara Faunal Subcomplex) infers a Late Pleistocene age and represents the richest deposit of Quaternary mammals reported in the central Campidano area.